Computed tomography-based body composition measures in COPD and their association with clinical outcomes: A systematic review. (3rd October 2022) - Nicholson, John M; Orsso, Camila E; Nourouzpour, Sahar; Elangeswaran, Brenawen; Chohan, Karan; Orchanian-Cheff, Ani; Fidler, Lee; Mathur, Sunita; Rozenberg, Dmitry
Background: Computed tomography (CT) is commonly utilized in chronic obstructive pulmonary disease (COPD) for lung cancer screening and emphysema characterization. Computed tomography-morphometric analysis of body composition (muscle mass and adiposity) has gained increased recognition as a marker of disease severity and prognosis. This systematic review aimed to describe the CT-methodology used to assess body composition and identify the association of body composition measures and disease severity, health-related quality of life (HRQL), cardiometabolic risk factors, respiratory exacerbations, and survival in patients with COPD. Methods: Six databases were searched (inception-September 2021) for studies evaluating adult COPD patients using thoracic or abdominal CT-muscle or adiposity body composition measures. The systematic review was conducted in accordance with the PRISMA guidelines. Results: Twenty eight articles were included with 15, 431 COPD patients, across all GOLD stages with 77% males, age range (mean/median 59–78 years), and BMI range 19.8–29.3 kg/m 2 . There was heterogeneity in assessment of muscle mass and adiposity using thoracic ( n = 22) and abdominal ( n = 8) CT-scans, capturing different muscle groups, anatomic locations, and adiposity compartments (visceral, subcutaneous, and epicardial). Low muscle mass and increased adiposity were associated with increased COPD severity measures (lung function, exercise capacity, dyspnea) and lower HRQL, but were not consistent across studies. Increased visceral adiposity ( n = 6) was associated with cardiovascular disease or risk factors (hypertension, hyperlipidemia, and diabetes). Low muscle CSA was prognostic of respiratory exacerbations or mortality in three of six studies, whereas the relationship with increased intermuscular adiposity and greater mortality was only observed in one of three studies. Conclusion: There was significant variability in CT-body composition measures. In several studies, low muscle mass was associated with increased disease severity and lower HRQL, whereas adiposity with cardiovascular disease/risk factors. Given the heterogeneity in body composition measures and clinical outcomes, the prognostic utility of CT-body composition in COPD requires further study.